(untitled) (Zoological Archives: An International Journal, 2026)
Bone density – quantified as bone mineral density (BMD) and bone volume fraction (BV/TV) – varies substantially across mammalian taxa in relation to body mass, locomotor mode, diet, and phylogenetic affinity, reflecting the biomechanical demands of diverse ecological niches. This study conducted the most comprehensive comparative analysis of mammalian bone density to date, quantifying BMD (dual-energy X-ray absorptiometry, DXA) and trabecular microarchitecture (microCT; 14 structural parameters) from 1,284 femur and lumbar vertebra specimens representing 84 species across 14 mammalian orders from eight European natural history collections. Body mass explained 68.4% of variance in cortical bone thickness (allometric slope = 0.38 +/- 0.02 on log-log axes), while locomotor category explained an additional 18.4% of variance after controlling for body mass (semi-aquatic species showing densest bone, fossorial species intermediate, cursorial lowest for equivalent mass; F3,76 = 28.4, p < 0.001). Trabecular bone volume fraction (BV/TV) was highest in compression-loaded vertebrae of heavy semi-aquatic mammals (mean 42.4 +/- 6.4%) and lowest in long bones of small arboreal mammals (mean 12.4 +/- 3.2%). Phylogenetically controlled regression confirmed locomotor mode as an independent predictor of bone density beyond body mass and diet (PGLS partial r = 0.62, p < 0.001). These results provide the most extensive reference dataset for mammalian comparative bone biomechanics, with applications to vertebrate palaeobiology, clinical comparative medicine, and the interpretation of fossil bone density as a proxy for locomotor ecology.